Pendinginan panel surya menggunakan kotak pendingin dan sirip pendingin - Gunawan Rudi Cahyono; Pathur Razi Ansyah; Nuryasin Qadimil Awaly (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2021)
An alternative energy source that can be utilized in Indonesia is solar energy, this energy is obtained from the intensity of solar radiation and then, is converted into electrical energy with solar panels technology. The performance of the solar panel is strongly influenced by the surface temperature of the panel because the semiconductor material in the panel is sensitive to temperature changes. However, the cooling process in solar panels to maintain temperature panels is important. This study combines the use of a cooling box and fins by considering fins with a very limited area. Experiments were carried out to observe natural and forced convection with or without fins in a cooling box. The results obtained that the natural convection cooling process of the panels using the cooling box and fins (without airflow) can reduce the temperature of the solar panels by 3.52%, on the other hand, by using forced convection process (with airflow), the cooling box and fins can reduce the temperature of solar panels by 3.78%. The effectiveness of fins in the case without airflow is 24.63%, but then the case of airflow cooling of solar panels is 16.63%. The addition of fins on natural convection cooling (without airflow) of solar panels causes the heat transfer area to increase, thereby increasing the rate of heat transfer between the solar panels and the air.